Can social norms promote sustainable food consumption? A systematic review - Daniele Pollicino; Heidi Zamzow; Ganga Shreedhar; Matteo M. Galizzi; Huseyin Naci; Patricia Freitag (Social Influence)
As societies shift toward plant-based diets to address sustainability challenges, social norms have emerged as influential in promoting sustainable food choices. However, there is limited synthesis on the effectiveness of related interventions. This review evaluates existing studies aiming to reduce animal-based consumption and/or increase plant-based choices within the context of climate change. We searched five databases, gray literature, and contacted authors to collect relevant studies, identifying 23 articles (34 studies). Research interest has grown since 2017, but findings suggest that social norm-based interventions have had limited success. We highlight key opportunities for future research, including better identification of referent groups tailored to specific population segments.